Annual Summary of Vital Statistics: 2012–2013 - Osterman, Michelle J.K. (Pediatrics, 2015)
The number of births in the United States declined by 1% between 2012 and 2013, to a total of 3 932 181. The general fertility rate also declined 1% to 62.5 births per 1000 women, the lowest rate ever reported. The total fertility rate was down by 1% in 2013 (to 1857.5 births per 1000 women). The teenage birth rate fell to another historic low in 2013, 26.5 births per 1000 women. Birth rates also declined for women 20 to 29 years, but the rates rose for women 30 to 39 and were unchanged for women 40 to 44. The percentage of all births that were to unmarried women declined slightly to 40.6% in 2013, from 40.7% in 2012. In 2013, the cesarean delivery rate declined to 32.7% from 32.8% for 2012. The preterm birth rate declined for the seventh straight year in 2013 to 11.39%; the low birth weight (LBW) rate was essentially unchanged at 8.02%. The infant mortality rate was 5.96 infant deaths per 1000 live births in 2013, down 13% from 2005 (6.86). The age-adjusted death rate for 2013 was 7.3 deaths per 1000 population, unchanged from 2012. Crude death rates for children aged 1 to 19 years declined to 24.0 per 100 000 population in 2013, from 24.8 in 2012. Unintentional injuries and suicide were, respectively, the first and second leading causes of death in this age group. These 2 causes of death jointly accounted for 45.7% of all deaths to children and adolescents in 2013.